2010
DOI: 10.4137/sti.s3994
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Pathways Leading to Heat Shock Transcription

Abstract: Heat shock proteins (HSP) are essential for intracellular protein folding during stress and protect cells from denaturation and aggregation cascades that can lead to cell death. HSP genes are regulated at the transcriptional level by heat shock transcription factor 1 (HSF1) that is activated by stress and binds to heat shock elements in HSP genes. The activation of HSF1 during heat shock involves conversion from an inert monomer to a DNA binding trimer through a series of intramolecular folding rearrangements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 85 publications
(203 reference statements)
0
81
0
Order By: Relevance
“…These results suggest that p38 (primarily p38␣) or one of its downstream targets participates in LPS-induced phosphorylation of histone H3 on the Hsp70 chromatin, recruitment of HSF1, and transcriptional activation of Hsp70. However, we have not excluded the contribution of additional HSF1 and histone modifications including HSF1 sumoylation (62,63) and histone acetylation and methylation (42,49,54,64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that p38 (primarily p38␣) or one of its downstream targets participates in LPS-induced phosphorylation of histone H3 on the Hsp70 chromatin, recruitment of HSF1, and transcriptional activation of Hsp70. However, we have not excluded the contribution of additional HSF1 and histone modifications including HSF1 sumoylation (62,63) and histone acetylation and methylation (42,49,54,64).…”
Section: Discussionmentioning
confidence: 99%
“…Because the transcriptional activation of Hsp genes is regulated by the stress-activated transcription factor, HSF1, which itself is regulated by post-translational modification including phosphorylation (18,48,49), we analyzed whether the TLR agonists stimulated post-translational modification of HSF1. We found that RAW cells stimulated with TLR1/2 and TLR 4 agonists at 37°C caused a distinct shift in HSF1 mobility on SDS and on two-dimensional gels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K inhibition also caused strong decreases in the level of Hsp27, another HSF1-regulated heat shock protein ( Figure 4). Because GSK3b has been reported to have a role in the stability of HSF1 [26][27][28] we tested whether dephosphorylated (i.e. active) GSK3b might be involved in the down-regulation of HSF1.…”
Section: Concomitant Hsp72/hsp73 Inhibition Significantly Enhances Apmentioning
confidence: 99%
“…5 HSPs are stress proteins whose synthesis is exaggerated by proteotoxic stresses such as heat shock. 6 The superfamily members, based on their molecular weight, include HSP90, HSP70, HSP60, HSP40 and small HSPs including HSP27. 7 HSP60, a typical mitochondrial chaperone, is associated with progression of diverse cancers.…”
Section: Introductionmentioning
confidence: 99%